Dermoscopy as a useful tool for short term monitoring of infantile hemangioma after oral propranolol onset. - Nakazono, M.; Kagimoto, S.; Nakamura, S.; Koike, T.; Maegawa, J. (European Journal of Pediatric Dermatology, 2022)
Oral propranolol (OP) remains the first-line treatment for problematic infantile hemangiomas (IHs). However, the efficacy of OP for IH varies among patients, with reports suggesting that some lesions are resistant to OP. Therefore, monitoring methods for accurate evaluation are particularly important issue, especially during the OP introduction period. Dermoscopy, a noninvasive and simple technique for various skin disorders, can occasionally be used for the longterm evaluation of OP treatment. We present five cases of patients with IHs who were started on OP treatment and monitored using a dermoscopic camera during the titolation period. In all lesions, a very early reaction to OP could be detected. Involution was noted 4 days after OP initiation in four lesions, and after 1 week in one lesion. Changes were more obvious in the dermoscopic images than in clinical images. Reduction of erythema was the main change and was apparent at the edge of the lesion. Dermoscopy might be superior to other assessment modalities given its ability for the detection of the early detailed changes in response to OP.